Formulasi dan Uji Aktivitas Antibakteri Sediaan Gel Antijerawat Ekstrak Etanol Daun Sisik Naga (Drymoglossum piloselloides (L.) Pressl.) terhadap Staphylococcus aureus - Suharyanisa Suharyanisa; Widya Fitri; Nuranti Rumela; Betharina br Tarigan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Acne appears due to increased sebum production on the skin and the growth of Staphylococcus aureus bacteria. The antibacterial activity of ethanol extract of dragon scale leaves (EEDSL) against Staphylococcus aureus bacteria provides strong inhibitory power. Dragon scale leaves (Drymoglossum piloselloides(L.) Pressl.)) can act as an anti-acne and its use as a preparation has not been widely carried out. This study aims to determine that EEDSL can be formulated as a gel preparation that meets the physicochemical quality requirements and that EEDSL gel preparations have antibacterial activity against Staphylococcus aureus. This study was conducted using an experimental method, sampling using the purposive sampling method in Kidupen Village, Juhar District, Karo Regency. Dragon scale leaf extract was obtained using the maceration technique with an ethanol solvent. EEDSL was formulated into a gel and then subjected to physical evaluation tests and antibacterial tests on staphylococcus aureus bacteria by looking at the diameter of the inhibitory power formed. The results of the study showed that the formulation of the anti-acne gel preparation was colorless, clear, and odorless obtained at F0. At F1; F2; and F3, a brown gel preparation was obtained with a semi-solid form and a distinctive EEDSL smell. The antibacterial activity test of EEDSL against Staphylococcus aureus showed an average value ± SD of the inhibition zone in each formula, namely at F0: 0.00 ± 0.00 mm; F1: 6.86 ± 0.17 mm; F2: 8.46 ± 0.19 mm; F3: 9.17 ± 0.18 mm; and positive control: 14.09 ± 0.23 mm. Based on the results of the data obtained, it can be concluded that EEDSL can be formulated as a gel preparation that meets the physicochemical quality requirements. Each concentration of ethanol extract of dragon scale leaves (Drymoglossum piloselloides (L.) Pressl.) has antibacterial activity against Staphylococcus aureus with a medium category.